The lithogeochemical signatures of hydrothermal alteration in the Waihi epithermal district, New Zealand. Issue 4 (2nd October 2019) - Barker, Shaun L.L.; Hood, Shawn; Hughes, Rosie M.; Richards, Shannon
ABSTRACT: Whole rock lithogeochemical data from the andesite rocks which host low-sulfidation epithermal gold veins in the Waihi district, New Zealand have been used to interpret hydrothermal alteration processes that variably altered the andesite rocks. The andesite host rocks are interpreted to have similar primary chemical compositions throughout the Waihi area, as reflected in similar ratios of immobile elements (eg Zr, Ti and other high field strength elements). The geochemical data reveal that elevated K/Al ratios occur in rocks proximal to low-Au–Ag deposits, reflecting adularia alteration in the host rocks associated with the upflowing hydrothermal fluids. Silicification of host rocks is achieved both by the addition of SiO2, as well as the destruction of plagioclase (reflected in the loss of CaO and Na2 O). The rocks have been variably altered, with calcite and pyrite abundance reflecting the addition of carbon and sulphur. Pathfinder element (eg As, Sb) concentrations are variable across the district, with high pathfinder element concentrations interpreted to reflect proximity to hydrothermal fluid flow. Together, the results provide a district-scale overview of hydrothermal alteration at Waihi, and emphasise the utility of lithogeochemistry for classifying and quantifying hydrothermal alteration that can then be used to interpret hydrothermal processes and assist mineral exploration.